2009
DOI: 10.1016/j.otohns.2009.06.188
|View full text |Cite
|
Sign up to set email alerts
|

Auto‐Crosslinked Hyaluronan Gel Injections in Phonosurgery

Abstract: Adult idiopathic subglottic stenosis remains a rare entity. Fibrosis of the airway at the level of the cricoid results in narrowing of the airway and progressive dyspnoea. The aetiology remains uncertain but reflux and hormonal influences have recently been proposed. Multiple modalities including surgical excision, laser excision and balloon dilatation have been described. Additionally the adjunctive use of mitomycin or oestrogen has also been noted. From these options, cricotracheal resection and reconstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 0 publications
2
11
1
2
Order By: Relevance
“…The best postoperative voice outcomes were noted in patients with UVFP, which was consistent with literature reports of Friedman et al [22] and Reiter and Brosch [23]. Also, the best results were obtained in cases with small to moderate phonatory gap, as consistent with King and Simpson [24] and Molteni et al [25].…”
Section: Voice Outcome Assessment After Injection Laryngoplastysupporting
confidence: 88%
“…The best postoperative voice outcomes were noted in patients with UVFP, which was consistent with literature reports of Friedman et al [22] and Reiter and Brosch [23]. Also, the best results were obtained in cases with small to moderate phonatory gap, as consistent with King and Simpson [24] and Molteni et al [25].…”
Section: Voice Outcome Assessment After Injection Laryngoplastysupporting
confidence: 88%
“…Hyaluronic acid gels are animal‐ or bacterial‐derived variations of the naturally occurring extracellular matrix glycosaminoglycan found in human tissue. These have been shown to be both safe and effective for deep injection, with the substance lasting from 4 to 12 months …”
Section: Discussionmentioning
confidence: 99%
“…We focused on three singular treatment modalities in this study, primarily due to their prominence and reported value in the clinical literature. Consequently, it is unknown how type I thyroplasty, injection laryngoplasty, and graft implantation outcomes compare to other proposed approaches such as mucosal slicing, 24 pulsed dye laser irradiation, 38 steroid injection, 35 and superficial injection/implantation of hyaluronic acid‐based biomaterials 36, 37 or autologous fat. 27, 28, 33, 34 Further, we did not include combinative treatments, such as CO 2 laser excision followed by collagen injection, 19, 20 fascia implantation followed by fat injection, 32 or gelatin sponge implantation followed by fat injection; 26 each of which holds the conceptual appeal of simultaneously or sequentially tackling glottal incompetence and lamina propria issues, with possibly compounded benefit.…”
Section: Discussionmentioning
confidence: 99%
“…13 The classic medialization approaches of type I thyroplasty and injection laryngoplasty are familiar to most surgeons and generally considered robust. 14–18 Approaches to treatment of the lamina propria are more challenging and include scar/sulcus excision, 19–21 undermining and release, 22, 23 mucosal slicing, 24 superficial implantation of autologous fat, fascia, or other scaffold materials, 25–34 superficial injection of steroids or regenerative biomaterials, 35–37 and pulsed dye laser irradiation. 38…”
Section: Introductionmentioning
confidence: 99%